A rapid and low-cost nonlithographic method to fabricate biomedical microdevices for blood flow analysis - Pinto, Elmano (2015)
Microfluidic devices are electrical/mechanical systems that offer the ability to work with minimal sample volumes, short reactions times, and have the possibility to perform massive parallel operations. An important application of microfluidics is blood rheology in microdevices, which has played a key role in recent developments of lab-on-chip devices for blood sampling and analysis. The most popular and traditional method to fabricate these types of devices is the polydimethylsiloxane (PDMS) soft lithography technique, which requires molds, usually produced by photolithography. Although the research results are extremely encouraging, the high costs and time involved in the production of molds by photolithography is currently slowing down the development cycle of these types of devices. Here we present a simple, rapid, and low-cost nonlithographic technique to create microfluidic systems for biomedical applications. The results demonstrate the ability of the proposed method to perform cell free layer (CFL) measurements and the formation of microbubbles in continuous blood flow.